Impact Of Brain Gym Activity and Breathing Technique on Stress and Academic Procrastination Among Medical Students - Kadam, Tanaya Sanjay; Malawade, Mandar (Journal of Neonatal Surgery, 2025)
Objective: This study aims to evaluate how medical students' stress levels and academic procrastination tendencies are affected by the Brain Gym and Breathing Technique. Methods: Using breathing techniques and a brain gym, we suggest a method to help medical students reduce stress and procrastination. The practice sessions will last 30 minutes each and be held three times a week. Using breathing techniques and a brain gym, we suggest a method to help medical students reduce stress and procrastination. The practice sessions will last 30 minutes each and be held three times a week. Result: According to the results, medical students' stress levels, procrastination, and general quality of life were all significantly improved by the Brain Gym and Breathing Technique routine. A paired t-test was used to examine the collected data. Based on the statistical findings, there was a substantial reduction in academic procrastinating behavior (p-value <0.0001) and stress (p-value <0.00001). Conclusion: There is a connection between stress and academic procrastination among medical students, largely due to the intense academic demands they face. This study demonstrates that implementing a structured protocol can successfully reduce stress and enhance academic performance among medical students.